Altered Lymphatic Vessel Anatomy and Markedly Diminished Lymph Clearance in Affected Hands of Patients With Active Rheumatoid Arthritis. Issue 9 (28th August 2020) - Bell, Richard D.; Rahimi, Homaira; Kenney, H. Mark; Lieberman, Alicia A.; Wood, Ronald W.; Schwarz, Edward M.; Ritchlin, Christopher T.
Abstract : Objective: To assess differences between lymphatic function in the affected hands of rheumatoid arthritis (RA) patients with active synovitis and that of healthy controls, using indocyanine green (ICG) dye and near‐infrared (NIR) imaging. Methods: NIR imaging of the hands of 8 patients with active RA and 13 healthy controls was performed following web space injection of 0.1 ml of 100 μ M ICG. The percentage of ICG retention in the web spaces was determined by NIR imaging at baseline and at 7 days (±1 day) after the initial injections; image analysis provided contraction frequency. ICG+ lymphatic vessel (LV) length and branching architecture were assessed. Results: Retention of ICG in RA hands was higher compared to controls ( P < 0.01). The average contraction frequency of ICG+ LVs in RA patients and in controls did not differ (mean ± SD 0.53 ± 0.39 contractions/minute versus 0.51 ± 0.35 contractions/minute). Total ICG+ LV length in RA hands was lower compared to healthy controls (58.3 ± 15.0 cm versus 71.4 ± 16.1 cm; P < 0.001), concomitant with a decrease in the number of ICG+ basilic LVs in the hands of RA patients ( P < 0.05). Conclusion: Lymphatic drainage in the hands of RA patients with active disease was reduced compared to controls. This reduction was associated with a decrease in total length of ICG+ LVs on the dorsal surface of the hands, which continued to contract at a similar rate to that observed in controls. These findings provide a plausible mechanism for exacerbation of synovitis and joint damage, specifically the accumulation and retention of inflammatory cells and catabolic factors in RA joints due to impaired efferent lymphatic flow. NIR/ICG imaging of RA hands is feasible and warrants formal investigation as a primary outcome measure for arthritis disease severity and/or persistence in future clinical trials.